MECHANISMS FOR GENERATING AND MANAGING EXTRA-BUDGETARY REVENUES (THE CASE OF BUDGETARY ORGANIZATIONS) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article analyzes the mechanisms for generating and managing extra-budgetary funds in budgetary organizations. It examines existing problems – unclear accounting criteria, incorrect revenue recognition in educational institutions, and methodological shortcomings in the leasing of state property. To address these issues, the implementation of a unified state accounting system, revenue recognition based on the service period, and economic justification for leases are proposed. The research emphasizes the importance of modern management mechanisms for enhancing the financial autonomy and efficiency of budgetary organizations.